Correlation between corneal biomechanical and tomographic parameters in cataract patients - Jia-Xi Li; Yi-He Liu; Yu-Shi Liu; Zi-Yuan Liu; Xue-Min Li (International Journal of Ophthalmology)
AIM: To investigate the relationship between preoperative corneal biomechanical properties and corneal tomographic properties in cataract patients. METHODS: The study consisted of 59 eyes of 30 participants who were diagnosed as cataract in Peking University Third Hospital between September 2019 and November 2019. Stepwise multivariable linear regression analysis was calculated to determine the relationship between corneal biomechanical parameters and tomographic parameters. The patients were classified into three groups of with the rule (WTR) astigmatism, against the rule astigmatism and oblique astigmatism. And the differences in corneal parameters among different groups were compared. RESULTS: There were significant differences in the first applanation time (A1T), the first applanation length (A1L), corneal velocity during the first applanation (Vin), the second applanation time (A2T), highest concavity (HC) radius, displacement amount (DA), DA ratio, stiffness parameter A1 (SPA1) and integrated radius (IR) between oblique astigmatism patients and the other two groups. Total corneal steep meridian (K2) was negatively associated with A1L, A1T and corneal velocity during the second applanation (Vout). Patients with higher anterior corneal curvature had lower HC radius and central corneal thickness (CCT; P=0.001 and 0.006, respectively), while the Ambrosio relational thickness to the horizontal profile (ARTh) was higher than those with lower anterior corneal curvature (P=0.009). CONCLUSION: The study reveals that the elasticity of corneal collagen fibers is greater, but the viscoelasticity of cornea is smaller in patients with oblique astigmatism. There is no significant difference in ARTh between patients with different types of astigmatism, that is, the corneal biomechanical specificity of oblique astigmatism group is probably not caused by corneal thickness. Moreover, we find patients with higher anterior corneal curvature has lower HC radius and CCT but higher ARTh than those with lower anterior corneal curvature.